Exercise as a method to reduce the risk of oral cancer: A narrative review - Anis Irmawati; Lia Aulia Rachma; S. Sidarningsih; Muhammad Naufal Hatta; Ira Arundina; Mohammed Aljunaid (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2022)
Background: Cancer is a major cause of death worldwide. One of the most common forms of cancer is oral cancer, which can occur due to exposure to carcinogenic factors, such as tobacco cigarettes, alcohol, betel-nut chewing, ultraviolet rays or human papillomavirus infection. Physical exercise is known to have many benefits and can contribute to reducing the risk of cancer, minimising the side-effects of treatment and increasing the curative effect of cancer treatment. Purpose: This study aimed to explain the role of exercise as a method to reduce oral cancer risk. Reviews: Studies examining the impact of exercise on reducing oral cancer risk are currently limited due to a lack of research on this subject. However, according to several laboratory experimental research studies on Mus musculus test subjects, moderate-intensity exercise contributes to suppressing the proliferation and development of oral squamous epithelial cells, which can subsequently become cancer cells. Exercise can also increase intracellular proteins that can induce apoptosis in cells (e.g. wild protein p53, the ratio of Bax/Bcl-2, and caspase-3), and can also decrease p53 mutant expression and transformed cells that can trigger cancer. Exercise must be optimally performed to prevent or control cancer symptoms, although the exact duration and intensity of exercise required to reduce cancer risk in humans have not been established. Conclusion: Exercise plays a role in reducing oral cancer risk by inducing apoptosis and preventing the development of transformed cells that can lead to developing cancer.